Comparison of Two Different Dosing Regimens of Oral Tranexamic Acid in Treatment of Facial Melasma - Shahid, Saima; Akhtar, Aisha (Medical Journal of South Punjab, 2026)
Objective: To compare the effectiveness of oral tranexamic acid 250 mg twice daily and tranexamic acid 500 mg twice daily in patients with melasma using the mMASI score. Methodology: Randomized controlled trial conducted at dermatology department Pak Emirates Military Hospital Rawalpindi from January 2021 to December 2022 in one year duration. Participants were adults aged 18–40 diagnosed with moderate to severe melasma based on the Melasma Area and Severity Index (MASI). Using computer-generated randomization, patients were randomly assigned into two groups. Group A received oral TXA 250 mg twice daily, while Group B received oral TXA 500 mg twice daily for 12 weeks. Follow-up assessments were conducted every four weeks to determine the variation in MASI scores and monitor treatment adherence. Primary outcomes included the percentage reduction in MASI score at the end of 12 weeks. Results: In terms of treatment outcomes, 7 patients (23.3%) in Group A achieved mMASI-75, compared to 12 patients (40.0%) in Group B (p < 0.001) (Figure I). Further comparison of mMASI scores between the two groups is presented in Table II, showing that Group B demonstrated significantly better mMASI scores than Group A (p < 0.050). Conclusion: A 500 mg twice-daily dose of tranexamic acid (TXA) is more effective than 250 mg twice-daily in reducing melasma severity and improving quality of life, as shown by significant improvements in the Modified Melasma Area and Severity Index and Melasma Quality of Life scores over 12 weeks.